Insulin resistance as a potential driving force of parental obesity-induced adverse metabolic programming mechanisms in children with obesity - Lucía Jurado-Sumariva; Álvaro González-Domínguez; Otto Savolainen; Jesús Domínguez-Riscart; Rikard Landberg; Raúl González-Domínguez (BMC Medicine)
Abstract Background Parental obesity has been identified as one of the most important early risk factors for childhood obesity, but molecular mechanisms driving this greater predisposition remain to be elucidated. Methods In this study, we recruited a cohort comprising children with obesity (body mass index over two z-scores above the age/sex-adjusted mean of the Spanish reference population, age range: 6–12 years), born to parents with obesity (N = 18) or without obesity (N = 41), as well as matched healthy controls (N = 26). Plasma and erythrocyte samples were collected for comprehensive biochemical and metabolomics analyses, this latter by applying high-throughput liquid chromatography–mass spectrometry. Then, a combination of multivariate and univariate statistical tools was applied to unravel the molecular pathogenic impairments that parental obesity may imprint in the offspring. Results Interestingly, we found parental obesity to be associated with exacerbated unhealthy metabolic outcomes in the offspring with obesity, as mirrored in higher fasting insulin levels (p = 2.8 × 10−8) and HOMA-IR scores (p = 1.3 × 10−8). This was in turn accompanied by altered concentrations in 87 plasma and 51 erythroid metabolites (p < 0.05) involved in a variety of obesity-related pathways that are known to be tightly regulated by insulin action, namely energy-related metabolism, branched-chain amino acids, nitrogen homeostasis, redox systems, and steroid synthesis (i.e., steroid hormones, bile acids). Additional analyses demonstrated that most metabolomics associations were largely attenuated after adjusting for the HOMA-IR scores. Conclusions Therefore, we hypothesize that insulin resistance could be a major driving force in mediating deleterious programming mechanisms induced by parental obesity in the offspring.